pentingnya deeptalk dalam membangun kesehatan mental gen dan keterbukaan emosional genz - Afrianti, Mike (Maliki Interdisciplinary Journal, 2025)
Generation Z is referred to as a generation that grew up in the digital era with the ability to get information quickly, but often has difficulty expressing their feelings deeply. Conversations that emphasize honesty, empathy, and emotional connection can help individuals cope with mental stress and improve interpersonal relationships. The purpose of this study was to see how deep talk helps the mental health and emotional openness of Gen Z. This was done by reading literature and looking at social phenomena among students and adolescents. The results of the study showed that deep talk has the ability to create a safe environment where people can share their feelings, reduce anxiety, and increase empathy for each other. Therefore, as part of efforts to maintain Gen Z's mental health, it is important to promote a culture of more open and deep communication.